2019
DOI: 10.1016/j.eneco.2019.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Q-complementarity in household adoption of photovoltaics and electricity-intensive goods: The case of electric vehicles

Abstract: Photovoltaic (PV) units and electric vehicles (EVs) are two household goods that are the focus of much research, and many policy initiatives attempting to promote a more sustainable, low-carbon energy system. Despite both academic and practical interest in household adoption of PV units and EVs, potential linkages in these household decisions have only just begun to be explored. This paper presents q-complementarity between the goods as one possible form of a linkage between PV and EV purchases that is based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
1
4
0
1
Order By: Relevance
“…Many households have already combined their PV with further technologies or have thought a lot about how to do so in the future. To some extent this resonates with the finding of Cohen et al ( 2019 ) as there appears to be “q-complementarity” between investment in PV and in certain other electrical goods. Q-complementarity is said to occur when the welfare gain from adopting one good is increased by the welfare gain from adopting another good and vice versa.…”
Section: Discussionsupporting
confidence: 75%
“…Many households have already combined their PV with further technologies or have thought a lot about how to do so in the future. To some extent this resonates with the finding of Cohen et al ( 2019 ) as there appears to be “q-complementarity” between investment in PV and in certain other electrical goods. Q-complementarity is said to occur when the welfare gain from adopting one good is increased by the welfare gain from adopting another good and vice versa.…”
Section: Discussionsupporting
confidence: 75%
“…As noted, EVs may be increasingly considered as being a part of the residential energy management. In line with this, and related to positive spillover, Cohen et al (2019) found that adoption of EVs and adoption of a photovoltaics were positively correlated and, compared to those who did not own photovoltaics, those who owned photovoltaics were 21% more likely have plans to purchase an EV in the next five years. As such, the authors of the study argue that photovoltaics and EV technologies are q-complementary, which is the perceived benefits of one are (perceived to) increase with the adoption another.…”
Section: Does Buying or Owning An Ev Influence Other Behaviours?mentioning
confidence: 56%
“…Finally, as expected, households that own electricity-intensive appliances, such as swimming pools and three or more refrigerators, are more likely to only adopt PV. This is probably because they can increase the self-consumption of produced solar energy 29 . In addition to increasing the probability of adopting only PV, having a swimming pool also increases the probability of adopting both PV and EV, while having three or more refrigerators has an insignificant but positive effect on adopting both technologies.…”
Section: Resultsmentioning
confidence: 99%
“…High residential electricity consumption, which correlates with increased electricity bills, has also been identified as a crucial determinant for PV adoption in studies by Best et al 26 and Cohen et al 29 . These studies reveal that factors such as the size of the house, number of household members, and ownership of electricity-intensive appliances serve as strong predictors of PV ownership.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation